A dual-imaging framework for multi-scale measurements of fatigue crack evolution in metallic materials. (January 2021) - Dharmadhikari, Susheel; Keller, Eric; Ray, Asok; Basak, Amrita
Graphical abstract: Highlights: A novel open architecture in-situ dual-imaging fatigue testing setup is developed. Multiscale fatigue damage evolution is monitored along two perpendicular directions. A linear relationship between crack dimensions at two length scales is established. First-of-its-kind simultaneous measurements of short & long cracks are demonstrated. Abstract: This paper presents a dual-imaging methodology to investigate fatigue crack initiation & propagation along the lateral and transverse directions in Al7075 flat specimens having a one-sided V-notch. The framework consists of a confocal and a digital microscope. The confocal microscope can detect the short crack initiation at a length-scale of 3 µm while the digital microscope has the capability of reliably measuring cracks at a scale of 0.5 mm. The apparatus provides a unique advantage of characterizing the multi-scale fatigue crack evolution without any significant restrictions on maximum specimen size and maximum loading or frequency.